Pathogenesis of primary sclerosing cholangitis and advances in diagnosis and management - Eaton, John E; Talwalkar, Jayant A; Lazaridis, Konstantinos N; Gores, Gregory J; Lindor, Keith D (Gastroenterology (New York, N.Y. 1943), 2013)
Primary sclerosing cholangitis (PSC), first described in the mid-1850s, is a complex liver disease that is heterogeneous in its presentation. PSC is characterized by chronic cholestasis associated with chronic inflammation of the biliary epithelium, resulting in multifocal bile duct strictures that can affect the entire biliary tree. Chronic inflammation leads to fibrosis involving the hepatic parenchyma and biliary tree, which can lead to cirrhosis and malignancy. The etiology of PSC is not fully understood, which in part explains the lack of effective medical therapy for this condition. However, we have begun to better understand the molecular pathogenesis of PSC. The recognition of specific clinical subtypes and their pattern of progression could improve phenotypic and genotypic classification of the disease. We review our current understanding of this enigmatic disorder and discuss important topics for future studies.